2003
DOI: 10.2169/internalmedicine.42.636
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Bronchial Asthma: Airway Inflammation and Hyperresponsiveness

Abstract: The international consensus report on diagnosis and treatment of asthma was published in 1992 (Clin ExpAllergy 22: 1-72). According to the report, asthma is a chronic inflammatory disorder of the airways in which many cells play a role, including mast cells and eosinophils.Airway inflammation causes various symptoms of asthma which are usually associated with widespread but variable airflow obstruction and causes an associated increase in airway responsiveness to a variety of stimuli. The definition of asthma,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0
6

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 36 publications
2
31
0
6
Order By: Relevance
“…Allergic asthma is a pathological condition of the airways characterized by airway hyperresponsiveness (AHR), inflammation, and a cellular infiltrate dominated by eosinophils (1,2). During the past decade, the incidence and severity of allergic asthma has grown sharply (3).…”
Section: Introductionmentioning
confidence: 99%
“…Allergic asthma is a pathological condition of the airways characterized by airway hyperresponsiveness (AHR), inflammation, and a cellular infiltrate dominated by eosinophils (1,2). During the past decade, the incidence and severity of allergic asthma has grown sharply (3).…”
Section: Introductionmentioning
confidence: 99%
“…A sthma is an inflammatory condition of the airways characterized by bronchial hyperresponsiveness, infiltration of inflammatory cells, and airway remodeling (1)(2)(3). Increased airway smooth muscle mass is an important feature of airway remodeling and has been linked in different ways to asthma pathogenesis (4,5).…”
mentioning
confidence: 99%
“…Increased airway smooth muscle mass is an important feature of airway remodeling and has been linked in different ways to asthma pathogenesis (4,5). In the last decade, several studies have shown that airway smooth muscle cells (ASMC) 3 may contribute to airway inflammation through the release of cytokines and chemokines such as TNF-␣, IL-1␤, CCL11 (eotaxin), and CCL5 (RANTES) (6). ASMC were also shown to respond to a wide variety of immune mediators and to express receptors for several noninflammatory cytokines (7).…”
mentioning
confidence: 99%
“…천식 환자는 일반 적으로 기도 (airway)의 광범위한 수축을 보이며, 임상적으로 발작적인 호흡 곤란이나 기침, 천명음을 발생시킨다 2) . 면역학 적인 측면에서 천식의 형태는 Th2 반응에 기인하는 기도의 만성 염증 질환 (chronic inflammatory disorder)에 속하며, 이러한 만성 염증 질환에서 IgE 의존성 비만세포 (mast cell) 의 활성화 과정이 매우 중요한 것으로 알려져 있다 3,4) . 배 (梨, Pear)는 기원상으로 돌배 (일본배, 沙梨, Pyrus pyrifolia Nakai.…”
Section: 서 론unclassified